2015
DOI: 10.1146/annurev-publhealth-031914-122535
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Firearm Violence in the Twenty-First Century United States

Abstract: This brief review summarizes the basic epidemiology of firearm violence, a large and costly public health problem in the United States for which the mortality rate has remained unchanged for more than a decade. It presents findings for the present in light of recent trends. Risk for firearm violence varies substantially across demographic subsets of the population and between states in patterns that are quite different for suicide and homicide. Suicide is far more common than homicide and its rate is increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
154
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 243 publications
(161 citation statements)
references
References 55 publications
4
154
1
2
Order By: Relevance
“…Although relatively rare in the aggregate, violence stemming from handguns increases the likelihood that encounters will become lethal (Braga, 2012;DeLisi, Piquero, & Cardwell, 2014;Farrington, Loeber, Stallings, & Homish, 2012;Reich, Culross, & Behrman, 2002). As such, handgun carrying among adolescents is a serious public health concern (Blum, 2001;Fowler, Dahlberg, Haileyesus, & Annest, 2015;Muula, Rudatsikira, & Siziya, 2008;Siegel et al, 2014) and public policy issue (Barry et al, 2015;Braga, 2012;Cross & Pruitt, 2014;Kleck, 2005Kleck, , 2015Wintemute, 2015aWintemute, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although relatively rare in the aggregate, violence stemming from handguns increases the likelihood that encounters will become lethal (Braga, 2012;DeLisi, Piquero, & Cardwell, 2014;Farrington, Loeber, Stallings, & Homish, 2012;Reich, Culross, & Behrman, 2002). As such, handgun carrying among adolescents is a serious public health concern (Blum, 2001;Fowler, Dahlberg, Haileyesus, & Annest, 2015;Muula, Rudatsikira, & Siziya, 2008;Siegel et al, 2014) and public policy issue (Barry et al, 2015;Braga, 2012;Cross & Pruitt, 2014;Kleck, 2005Kleck, , 2015Wintemute, 2015aWintemute, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Firearm violence prevalence rises steeply during adolescence and young adulthood then falls thereafter (Wintemute, 2015a). In addition to males more likely to carry handgun than females (Pickett et al, 2005), research has identified racial and ethnic differences.…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk for firearm-related homicide is highest among young African American men, most firearm-related deaths are suicides, for which older white men are at highest risk (2). Public mass shootings account for a small percentage of firearmrelated deaths but are occurring more frequently and could affect the character of public life in the United States (3).…”
mentioning
confidence: 99%
“…Firearm violence is among the leading causes of death among teens and young adults of all races and is the number one cause of mortality overall among African American men ages 15-34. 1 As with many other health indicators, the USA is an outlier (in the wrong direction) when compared with other industrialized economies. Firearm-associated homicide and suicide rates far exceed those of our peer nations.…”
mentioning
confidence: 99%
“…Firearm-associated homicide and suicide rates far exceed those of our peer nations. 1 Over the past 50 years, there have been 126 mass shooting events in the US that have claimed the lives of 869 people. A total of 244 guns were used (each shooter brought an average of 4 guns to each massacre); 39 of the guns were obtained illegally.…”
mentioning
confidence: 99%